The Dominant Role of Forensic Evidence in Multidimensional Crimes Over Other Types of Evidence in Sexual Violence, Torture, Rape and Killing against Women and Children: Dr Aftab Ahmad Malik - Malik, Dr Aftab Ahmad (International Journal for Electronic Crime Investigation, 2021)
Abstract: The trend in multidimensional crimes of Sexual Violence, Torture, Rape and Killing of Innocent Women and Children is exponentially increasing. The impact in the society is extremely adverse and unhealthy causing agony and mental torture to the common person. The life of citizens, women and children is not safe. The abduction of children under 16 accompanied with rape and torturous killing is becoming prominent and similarly women are victims. Their dead bodies are normally disposed of near city/village waste filth depot. On the other hand, children of religious schools mostly orphans are victims of “religious instructors”, who are apparently out of the scope of law enforcing agencies. The “religious instructors” inflict and impose rigorous punishments including Sexual Violence, Torture, Rape and Killing. The character of “religious instructors” of the privately managed schools (madrassas) seems highly unreliable. The voice of their victims not heard in the nearby surroundings and neighborhood of society. Some rich and influential people with a blend of western culture, living without peace of mind are involved in heinous, monstrous, atrocious, odious, terrible multidimensional crimes of Sexual Violence, Torture, Rape and Killing of Innocent Women and Children. The authors of this paper have been advocating that the state, courts and law enforcement agencies must implement a strong deterrent strategy, preventive measures with restrictive approach to restrain such crimes. There must exist a real deterrent force in society to combat such crimes committed in series. The paper presents case studies to analyze and compare circumstantial evidence, the forensic evidence with that evidence tendered by eye- witnesses. Can the prosecution entirely rely upon the forensic evidence and circumstantial evidence in court of law? The paper addresses this question of law. The most sever part of the our assertion is who will control heinous offences of abduction, sexual violence, torture, rape and killing of innocent women and children, the legislation, the executive of the country, the courts or the law enforcement agencies?